The Effects of Substitution on Fish Meal with Maggot Meal in Artificial Feedfor Eels (Anguilla bicolor) Growth and Survival Rate - ahmad, ananda; Sukardi, Purnama; Nugrayani, Dewi; Trianingtyas, Laela (PT. Artha GenetikaLab Indonesia, 2025)
Eel (Anguilla sp.) is a leading freshwater fish commodity. In the intensivesystem, high stocking density results in high production costs. Maggot meal isan alternative raw material that has complete nutritional value such as fishmeal but is cheaper. The purpose of this study was to determine theeffectiveness of substituted fish meal with maggot meal on the growth andsurvival rate (Anguilla bicolor) Elver phase. The method carried out in thisstudy used an experimental method with a completely randomized design(CRD) consisting of 4 treatments and 3 replications with a combination of fishmeal and maggot meal, P0: 100% TI and 0% TM, P1: 80% TI and 20% TM,P2: TI 60% and TM 40% and P3: TI 40% and TM 60%. The results of rearingfor 60 days showed a significant effect on absolute weight growth, specificgrowth rate, and yield, while the yield had no significant effect on absolutelength growth, feed conversion, and survival. The results of the water qualityparameters of the media are temperatures ranging from 24 °C -29,8 °C, pHranging from 5,14-7,7, DO ranging from 2,4 mg/l – 5,1 mg/l and ammoniaranging from 0 ppm – 0,01 ppm.